Factors Influencing Employee Engagement in Energy & Utilities Company in Malaysia - Siti Maizatul Akma, Muriza (2023)
The well being of an organization and the success of the company can be influenced by the level of employee engagement among their employees. The employees that feel engaged, their motivation level increase and they tend to commit to their work. Employee engagement also is one of the reasons employees can pay more attention when they are working which leads to high productivity while the organization’s goal can be achieved together at the same time the number of resignation can be reduced. Therefore, this research was to determine the factors influencing employee engagement. This research paper was carried out among employees in a private sector which is Energy & Utilities Company. A quantitative research method was employed in which questionnaire as the main instrument. This study examined the four independent variables which are organizational leadership, rewards and recognition, professional development and training, and effective communication that influence the dependent variable, employee engagement. Questionnaires have been distributed and 247 employees in Energy & Utilities Company have answered via online platform which is SurveyMonkey. The collect data was analyses using Smart-PLS. Findings of the the research revealed that only three variables gives significant to the employee engagement while professional development and training as one of the factor is not accepted. Discussion on findings, implication of study and recommendation for future also highlighted toward the end of the research paper.